Proving in Geometry: A Sociocultural Approach to Constructing Mathematical Arguments through Multimodal Literacies - Taylor, Christine (Journal of adolescent & adult literacy, 2018)
Multimodal literacies have been incorporated as social learning practices in content areas, but research regarding multimodality within secondary mathematics instruction has often lacked the sociocultural lens. The author describes practitioner action research in the form of a case study (with one focal participant) from a public high school. The author explored the use of multimodal literacies through geometry students' projects, work samples, classroom videos, and interviews. Students created and presented arguments (through PowerPoint, Word, videos, and storybooks) on court cases in efforts to relate proving and justifying in geometry to evidence and claims in court. Findings reveal ways that multimodal literacies served as a vehicle for students to engage with their social context of learning in a mathematics classroom, demonstrating that sociocultural approaches to multimodal literacies can apprentice students into disciplinary literacy practices of mathematics. Moreover, these sociocultural perspectives toward multimodal literacies pose possible instructional applications in multiple content areas.